The influence of accounting information quality and internal control on stock price synchronicity: evidence from China A-share ChiNext market - Shen, Er (2023)
In the capital market, the stock prices synchronicity is an important indicator to measure the "simultaneously rise and fall" of individual stocks to the average market trend. Since the accounting reform in 2007, China's accounting standards have been gradually integrating with IFRS, thereby improving the quality of financial statements. However, the deficiencies in the internal control construction and external supervision of listed companies have led to numerous noise transactions and have slowed down the pace of transformation to a mature market. Especially for ChiNext, a stock market with relatively high investment risk, constantly improving accounting systems and high noise environment phenomena coexist.